A Synthetic, Stock-Flow Consistent Macroeconomic Model of Financialisation - Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2007)
This article is centred around the notions of shareholder value orientation and financialisation. Shareholder value orientation is reflected by a high dividend payout ratio applied by firms and the reluctance of firms to finance physical investment via new equity issues. Financialisation is the more general development towards an increased importance of the financial sector of the economy relative to the non-financial sector. In this article, a synthetic, stock-flow consistent model is developed that attempts to encompass and at times adjust some important recent works on the effects of financialisation. This includes contributions from the fields of mainstream information economics and Post Keynesian economics. We conduct simulations reflecting increased shareholder value orientation and show that the model produces a number of results that appear consistent with many stylised facts particularly of the US economy since the early 1980s.
urn:nbn:de:101:1-2008081853
Keywords: E10; E21; D14; G11; G32; G35; E25; 330; Stocks and Flows; Corporate Governance; Investment Finance; Payout Policy; Income Distribution